2011
DOI: 10.1007/s10838-011-9172-y
|View full text |Cite
|
Sign up to set email alerts
|

Matters of Interest: The Objects of Research in Science and Technoscience

Abstract: International audienceThis discussion paper proposes that a meaningful distinction between science and technoscience can be found at the level of the objects of research. Both notions intermingle in the attitudes, intentions, programs and projects of researchers and research institutions – that is, on the side of the subjects of research. But the difference between science and technoscience becomes more explicit when research results are presented in particular settings and when the objects of research are exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 26 publications
(12 reference statements)
0
18
0
1
Order By: Relevance
“…In contrast to the "traditional mode of doing science," in which scientific objects are relevant because there are facts about them, technoscience looks at the deep entanglements between theoretical representations (science) and technical interventions. Technoscience is, therefore, interested in things as configurations of different interests [2].…”
Section: Animals and Technosciencementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the "traditional mode of doing science," in which scientific objects are relevant because there are facts about them, technoscience looks at the deep entanglements between theoretical representations (science) and technical interventions. Technoscience is, therefore, interested in things as configurations of different interests [2].…”
Section: Animals and Technosciencementioning
confidence: 99%
“…The OncoMouse is a product of the knowledge economy and viewed by the researchers as an entirely self-sufficient system: rather than extrapolating general biological facts in order to apply them to humans is no longer; according to Haraway, biotechnologists are producing cures for the diseases of these particular "animal models" (cf. [2]). Here, we have to remember the sentence of a former director of the National Cancer Institute Richard Klausner to the Los Angeles Times: "The history of cancer research has been a history of curing cancer in the mouse.…”
Section: Animals and Technosciencementioning
confidence: 99%
“…Research on the history and sociology of innovation has shown, for instance, that basic and applied research are linked in the case of electromagnetism (Wise 1988), nuclear physics (Latour 1989), and materials science (Callon et al 1991;Bensaude-Vincent et al 2011). NST, however, does more than intertwining basic and applied modes of research.…”
Section: Introductionmentioning
confidence: 99%
“…While the category of 'basic science' always presupposes the need for a category of 'applied science'-and vice versa-the emergent and exploratory research conducted under the NST umbrella seems to belong to a regime of knowledge production that proves indifferent to these dichotomies. For that reason, some prefer to call this kind of knowledge regime 'technoscience', where theoretical representation and technical intervention cannot-even in thought-be distinguished (Bensaude-Vincent et al 2011). Indeed, a large proportion of nano-objects functioning in the lab (such as molecular machines or solidstate quantum computers) have no short or medium term applications: they could have applications-and of course some of them will-but they are not primarily designed or valued for utilitarian purposes (Loeve 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of discussing whether technoscience is an historical rupture or business as usual, the GOTO project assumes that: (1) Technoscience is a regime of research that is now dominant, although it can be instantiated in the past centuries; (2) At the ontological level, technoscience brings a specific mode of existence of objects (and of our co-existence with them) which is distinct from the mode of existence of scientific objects (Bensaude-Vincent et al 2011) as well as from the mode of existence of technical objects; (3) Instead of arguing pro or contra technoscience, the main task is to appraise and tame alternative modes of togetherness, worldliness and coexistence with objects.…”
mentioning
confidence: 99%